2012
DOI: 10.1002/adfm.201102510
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Structure with Function in Thermally Annealed PCDTBT:PC70BM Photovoltaic Blends

Abstract: A range of optical probes are used to study the nanoscale‐structure and electronic‐functionality of a photovoltaic‐applicable blend of the carbazole co‐polymer poly[N‐9′‐heptadecanyl‐2,7‐carbazole‐alt‐5,5‐(4′,7′‐di‐2‐thienyl‐2′,1′,3′‐benzothiadiazole) (PCDTBT) and the electronic accepting fullerene derivative (6,6)‐phenyl C70‐butyric acid methyl ester (PC70BM). In particular, it is shown that the glass transition temperature of a PCDTBT:PC70BM blend thin‐film is not sensitive to the relative blend‐ratio or fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
155
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(171 citation statements)
references
References 42 publications
16
155
0
Order By: Relevance
“…In contrast, the inclusion of a P3HT:PC 70 BM blend fi lm presents an opportunity to compare a blend fi lm in which the solubility of PC 70 BM in the polymer is lower than that of PCDTBT:PC 70 BM. [ 37,41,42 ] In Figure 7 , it can be seen that the evolution in X-ray scattering intensity in each sample for both solvent and PC 70 BM are broadly similar to the dynamics of PCDTBT:PC 70 BM; specifi cially an increase in scattering intensity from PC 70 BM aggregates is delayed with respect to the initial casting of the fi lm. Note, the exact time for the onset of rapid increase in the solid concentration of the PCDTBT-8:PC 70 BM fi lm appears to occur at an earlier time after fi lm casting than is observed in all the other blends studied.…”
Section: Drying Dynamics Of Pcdtbt-8 Meh-ppv and P3ht:pc 70 Bm Blmentioning
confidence: 81%
“…In contrast, the inclusion of a P3HT:PC 70 BM blend fi lm presents an opportunity to compare a blend fi lm in which the solubility of PC 70 BM in the polymer is lower than that of PCDTBT:PC 70 BM. [ 37,41,42 ] In Figure 7 , it can be seen that the evolution in X-ray scattering intensity in each sample for both solvent and PC 70 BM are broadly similar to the dynamics of PCDTBT:PC 70 BM; specifi cially an increase in scattering intensity from PC 70 BM aggregates is delayed with respect to the initial casting of the fi lm. Note, the exact time for the onset of rapid increase in the solid concentration of the PCDTBT-8:PC 70 BM fi lm appears to occur at an earlier time after fi lm casting than is observed in all the other blends studied.…”
Section: Drying Dynamics Of Pcdtbt-8 Meh-ppv and P3ht:pc 70 Bm Blmentioning
confidence: 81%
“…It was also shown that the glass transition temperature of the blend reduces upon annealing; an observation consistent with the disruption of π-π stacking between PCDTBT molecules. Reduced π-π stacking is correlated with reduced hole-mobility in thermally annealed films [128].…”
Section: Thermal Annealingmentioning
confidence: 96%
“…The test runs for 20 hours and the solar cells were illuminated to monitor the OPV performance for a total period shorter than 30 minutes, allowing to neglect the initial burn-in light induced degradation [20]. The following degradation effects on the photovoltaic parameters are expected: i) a reduction of the short circuit current density (J sc ) due to morphological changes of the BHJ blend [27,35,36] that can affect the charge mobility and the generation of a charge transfer complex; 38 ii) a variation of the open circuit voltage (V oc ) as a consequence of a different D:A phase segregation [56] and increase of defect states which controls the recombination [37]; iii) those phenomena can affect also the fill factor (FF), by a limitation of the charge transport and increase in the series resistance [38]. Fig 2. Fitting of the PCE data (Fig 2a) was carried out using an exponential decay: PCE = PCE f + (1-PCE f ) exp (-t/τ), where t represents the experiment time, PCE f is the final value attained by the efficiency and accounts for the percentage of the initial efficiency preserved after thermal degradation, while the time constant τ is the lifetime at which the efficiency value is decreased by a factor e, and allows to compare the kinetic of the PCE decay of each samples.…”
Section: Lifetime Studymentioning
confidence: 99%
“…However, degradation pathways due to light soaking and high temperature cannot be eliminated, and, in general, they induce morphology evolution of the active layer [27], interlayer and electrode diffusion [28], and electrode interaction with the organic materials [29]. The behavior of BHJ OPVs with thermal degradation is generally correlated to morphological changes occurring in the active layer that can affect: i) charge separation process by formation of fullerene aggregates in polymer:fullerene blends, which leads to a PCE loss due to the reduction of the donor:acceptor (D:A) interfacial area [30][31][32], ii) charge extraction by a migration of a skinlayer of either polymer [33] or fullerene [34] adhering to the top contact, generating barriers or selective transport regions as a function of the device architecture; iii) transport properties by modification of the polymer packing in the blend [35,36], iv) recombination by an increase of the number of defect states at the bulk of the active layer [37], v) optical properties by generation of a charge transfer complex between donor and acceptor molecules which also acts as an exciton quencher [38]. Several works [31,32] demonstrated that morphological reorganization processes occur only if the solar cell is subjected to temperatures near or above the glass transition temperature (Tg) of the donor polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation